A new species of the genus Mallomonas (Chrysophyceae: Synurales), Mallomonas kuzminii sp. nov., from lake Frolikha (Russia, Baikal region) - Gusev, Evgeniy Sergeevich; Kulikovskiy, Maxim Sergeevich (Phytotaxa, 2013)
Mallomonas kuzminii sp. nov. is described from an oligotrophic lake located in Russia, East Siberia, Northern Baikal region. The description is based on silica-scale morphology studied by means of transmission and scanning electron microscopy. This new species belongs to the section Mallomonas and has several types of scales with or without dome. The form of the scales, the strongly hooded V-rib, and a dome with ribs surrounded by the extensions of the anterior rib, are the main features which distinguish this new taxon from the other species of the section.